Rescue percutaneous transhepatic portal vein embolization after failed associated liver partition and portal vein ligation for staged hepatectomy in a patient with multiple liver metastases of rectal cancer: a case report - Hidenori Tomida; Tsuyhosi Notake; Akira Shimizu; Koji Kubota; Kentaro Umemura; Atsushi Kamachi; Takamune Goto; Shiori Yamazaki; Yuji Soejima (Surgical Case Reports)
Abstract Background Liver metastasis is the most common form of distant spread of colorectal cancer. Despite oncological and surgical advances, only about 25% of patients are eligible to undergo resection. As the liver has a limited resectable volume, tumor reduction and remnant liver hypertrophy are of critical importance in treating initially unresectable colorectal cancer liver metastasis. Associated liver partition and portal vein ligation for staged hepatectomy (ALPPS) allows rapid liver hypertrophy within a short period and has been reported to be useful in recent years. Case presentation A 29-year-old woman complaining of bloody stool was referred to our hospital. She was diagnosed with rectal cancer (Rb) with simultaneous multiple liver and lung metastases. The patient was then initially commenced on chemotherapy and completed it with a satisfactory response. Right trisectionectomy was necessary to achieve hepatic clearance; however, the future liver remnant (FLR) volume was insufficient. Therefore, we decided to perform totally laparoscopic ALPPS to obtain enough FLR volume. However, the FLR increase was slow, and FLR did not attain the required volume for right trisectionectomy. Computed tomography showed that right portal venous blood flow was increased via developed collateral vessels around the portal vein. We attempted to induce further liver growth by blocking portal blood flow using additional percutaneous transhepatic portal vein embolization (PTPE), and a rapid increase in FLR was obtained. The patient underwent right trisectionectomy and partial resection of S2 with negative margins, and the patient was discharged without postoperative liver failure. Conclusions Resumption of the portal venous blood flow through collateral vessels after ALPPS may have interfered with the planned residual liver hypertrophy. Performing PTPE in addition to ALPPS increased the FLR volume, and radical hepatectomy was completed safely. Remnant portal venous blood flow following ALPPS is an important issue to be considered in surgical planning, and early additional portal vein embolization could be effective.